Early life adversity and the specificity of autobiographical memory amongst people with schizophrenia. (May 2021) - Barry, Tom J.; Villanueva-Romero, Clara M.; Hernández-Viadel, Jose V.; Ricarte, Jorge J.
Abstract: Background: People with schizophrenia diagnoses are thought to have difficulty retrieving memories of specific autobiographical events because of attempts to avoid the negative affect associated with previous adversity. We provide the first investigation of the association between early adversity (e.g., childhood abuse) and autobiographical memory problems amongst people with and without schizophrenia. Method: Participants with diagnoses of schizophrenia ( n  = 79) and participants without diagnoses ( n  = 41) completed the Maltreatment and Abuse Chronology of Exposure (MACE) interview schedule and a cued recall task. Results: Participants exposed to greater number of, and more severe, childhood adversity retrieved fewer specific autobiographical memories. However, participants with schizophrenia retrieved fewer specific memories than control participants without diagnoses irrespective of the presence, severity or number of adversities they experienced. Conclusions: Adversity contributes towards autobiographical memory difficulty but adversity does not explain why people with schizophrenia differ from diagnoses-free people in their autobiographical memory abilities. Highlights: More severe adversity was associated with recall of fewer specific memories. Higher number of adversities also associated with worse recall. These effects did not differ for memories retrieved by positive or negative cues. Participants with schizophrenia recalled fewer specific memories than controls. This difference was independent of adversity severity or multiplicity.